PROBLEMS IN THE IMPLEMENTATION OF THE FULFILLMENT OF THE RIGHTS OF PRISONERS IN THE FIELD OF EDUCATION IN CLASS 1 SURABAYA CORRECTIONAL INSTITUTION - Leo Bagus Satriyo; Karim (DE RECHT (Journal of Police and Law Enforcement), 2024)
Education is very important, especially as the first step in forming a person's character. Based on the 1945 Constitution Number 20 of 2003 concerning the National Education System, obtaining education is a right for all citizens, including prisoners. This research aims to find out and examine the implementation of the fulfillment of prisoners' rights in the field of education at the Class 1 Correctional Institution in Surabaya. The research method used is empirical legal research using a qualitative descriptive approach. This research method places the law as a guideline for behavior in life which is always interacting and connected in social aspects. This research concludes that according to the author, the implementation of fulfilling prisoners' rights in the field of education at the Surabaya Class 1 Correctional Institution has been well structured in accordance with statutory regulations, but in its implementation there are still many obstacles. Even though there are obstacles, based on the results of the author's interviews with several prisoner representatives, prisoner development activity programs such as the Sekar Mentari Elementary School Equivalency Course (KPSD) and Pursuing Equivalency Program Examination (UPK) Packages A, B and Package C must still be implemented to fulfill prisoners' rights in the field of education.